Paramedic-led prehospital thrombolysis is safe and effective: the East Anglian experience. Issue 6 (22nd May 2009) - Khan, S N; Murray, P; McCormick, L; Sharples, L S; Salahshouri, P; Scott, J; Schofield, P M
Abstract : Introduction: Prehospital thrombolysis has been shown to improve patient outcomes in clinical trials and this has been confirmed in the ongoing large national myocardial infarction registry (Myocardial Infarction National Audit Project; MINAP) reports. This paper describes a system to improve the delivery of prehospital thrombolysis and the associated governance requirements to gain maximum patient benefit. Methods: Demographic data were prospectively collected on all patients treated by the East Anglian Ambulance Trust with bolus thrombolytics for a presumed diagnosis of ST elevation myocardial infarction between November 2003 and February 2007. Survival status was determined from the NHS strategic tracing service. Results: 1062 patients (mean age 64.0 years (SD 10.6), 795 men) were treated in this time period. There were 71 deaths in this group, with actuarial survival of 93.9% (SE 0.9%) at 30 days, 91.7% (SE 1.0%) at 6 months and 90.8% (SE 1.1%) at 12 months after treatment. Age and cardiac arrest were most strongly associated with mortality (both p<0.001). Twelve (1.2%) patients received thrombolysis that on review was considered inappropriate. There were no deaths in this subgroup. Conclusions: Prehospital thrombolysis can be administered safely by ambulance staff supported by a Trust clinical support system with excellent clinical outcomes.